PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP TINGKAT KREATIVITAS GURU SD NEGERI 060800 KECAMATAN MEDAN AREA T.A. 2020 / 2021 - Tina Sitompul; Ulfah Rezeki; Siti Harahap (JURNAL CURERE, 2021)
Teacher learning creativity is often a topic of discussion by various parties, because it is considered to determine the achievement of educational outcomes. The teacher is the spearhead of the ongoing learning activities. Based on the results of observations in March 2021 that have been carried out by researchers at SD Negeri 060800, Medan Area District, it is very clear that teacher creativity still needs to be improved. Judging from the number of existing class teachers, namely 15 classroom teachers, there are only about 13% of classroom teachers who have high creativity and have won the competition for outstanding and creative teachers at the Medan Area District level, while 87% of the number of classroom teachers are still lacking and need to be improved. his creativity. Low teacher learning creativity, among others, is manifested through actions of lack of care, just carrying out tasks, orientation to low achievement, low productivity, less efficient and effective, lack of discipline, boring students and so on.Factors that influence teacher creativity include: internal factors (inheritance and psychological), namely, intelligence which includes verbal ability, fluent thinking, knowledge, problem formulation, strategy formulation, mental representation, decision-making skills and balance and general intellectual integration, and cognitive or intellectual style, which includes slack and convertible attachment, creating one's own rules, doing things one's own way and preferring less structured problems. The dimensions of personality and motivation include traits such as flexibility, drive for achievement and recognition of tenacity in facing obstacles and taking moderate risks. External factors (social and cultural environment), namely, teacher educational background, teacher trainings and teacher organizations, teacher teaching experience, and teacher welfare factors.